Paul Klee - Venezia, Mike. (Chicago : Children's Press, 1991)
Discusses, in simple text, the life and work of the abstract painter, focusing on his use of color, shape, and symbolism.
Wilson's Children.
5.3
K-3
P-4.
Keywords: Klee, Paul, -- 1879-1940 -- Juvenile literature; Klee, Paul, -- 1879-1940.; Klee, Paul, -- 1879-1940.; Painters -- Germany -- Biography -- Juvenile literature; Painting -- Appreciation -- Juvenile literature; Art appreciation; Artists; Painting, German; Painting, Modern -- Germany; Art appreciation; German painting; Modern painting; Painters -- Germany -- Biography